Ziarah sebagai Komunikasi Vertikal: Makna Pemilihan Hari dalam Tradisi Religius Masyarakat Padureso - Ukti Faiqoh (Lakpesdam PCNU Kota Salatiga, 2023)
This study examines the grave pilgrimage (ziarah kubur) tradition among the Nahdlatul Ulama (NU) community in Padureso, Temanggung, focusing on the symbolic meaning of selecting specific sacred days such as Friday Legi and Tuesday Kliwon night. This tradition is understood not merely as a cultural habit but as a form of vertical spiritual communication between humans and God, rooted in the integration of Islamic teachings and Javanese cosmology. Employing a qualitative ethnographic approach, data were collected through participant observation, in-depth interviews with religious leaders and NU community members, and literature review on pilgrimage traditions, sacred time, and Islam Nusantara. Data analysis was conducted using an interpretative framework of ritual communication phenomenology. The findings reveal that the selection of pilgrimage days reflects a collective religious consciousness aimed at enhancing spiritual devotion, strengthening transcendental relations with God, and reinforcing social cohesion within the NU community. This tradition represents a contextual and symbolic expression of Islam Nusantara that harmonizes Islamic theology, local culture, and communal religious life.